Identifying Potential Fungi Species Through Molecular Approach and Its Biosurfactants Production - Wong, Yieng Yong (2017)
There are approximately 1.5.-5 million of fungal species present worldwide. However, actually only 5% of the fungi have been classified accordingly. Basic classification of fungi species was based on morphology characteristics identification but this is an inaccurate approach due to certain fungi species only presence of limited morphological characteristics. With the development of sciences and new technologies nowadays, researchers are able to discover molecular identification approach of the fungi based on DNA extracted. Hence, identification of the fungi species would be more accurate. Biosurfactant was well known on bioremediation on the polluted environment such as heavy metal polluted soil. The aims of this experience were to determine the fungal species obtained from Aeyna Metal Trading in Shah Alam through molecular identification approach and to identify the ability of those fungal species to produce the biosurfactant. Twelve different fungal species were identified. Unfortunately, the DNA was only extracted from the eight fungal samples and identified by molecular approach. The query sequence that compared by using bioinformatics tool BLAST consisted of up to 99% of identifies were chosen namely Trichoderma erinaceum, Trichoderma longibrachiatum, Penicillum simplissimum, Aspergillus niger, Hypocrea koningii , Aspergillus ustus and Gongronell butleri. Another four fungi species were identified through macroscopic and microscopic identification by previous senior namely Penicillium chrysogenum , Aspergillus nidulans, Fusarium oxysporum and Aspergillus flavus. Three methods were carried out to detect the production of biosurfactants by each of these fungal species. Oil Spreading method and Drop Collapse method showed negative results for all species while Emulsifying Index method showed positive results for all fungal species except for Gongronella butleri. Among these species, Penicillium chrysogenum produced most biosurfactants while Gongronella butleri produced no biosurfactant. Identifying the exact species can identify the potential of the fungi species to produce biosurfactant.